Pengaruh Kualitas Pelayanan dan Fasilitas Melalui Electronic Word of Mouth Terhadap Kepuasan Pelanggan di Kedai Mungil Davanka Putri - Chayani Farhanah Putri; Hadita Hadita; Neng Siti Komariah; Novita Wahyu Setyawati; Jumawan Jumawan (Yayasan Inovasi Akademi Nusantara, 2025)
The quantitative research method is a research approach that uses data, with a focus on measuring objective results and statistical analysis. Quantitative research also includes questions or statements that have been provided with a choice of numbers for each score. A total of 102 samples were used, the purpose of this study was to find and test the hypothesis. The tool used to assist the research process was Smart Pls version 4. The results of this study show that Service Quality has a direct and significant effect on EWOM, Facilities have a direct and significant effect on EWOM, Service Quality has no direct and insignificant effect on Customer Satisfaction, Facilities have a direct and significant effect on Customer Satisfaction, and EWOM has a direct and significant effect on Customer Satisfaction.